– Polityka medialna Kościoła a świat polityki w świetle wybranych dokumentów Papieskiej Rady ds. Środków Społecznego Przekazu - Grochowski, Robert (Fides, Ratio et Patria. Studia Toruńskie, 2017)
Catholic Church launches its strengthening relating to principles and standards that should be respected in policy passed by the media. There are, of course, legal acts, where respect must be ordered. Their observance, as opposed to the typical acts depends entirely on the good will and conscience. These ecclesiastical documents should include first and foremost the rules and principles laid down by the Papal Council. Measures of social media and the accompanying documents. The provisions of these entries refer to the Church of their relationship with the world of politics and its other social goods. You should also check that the Second Vatican Council has already determined that the Church has almost a duty to engage in politics.Based on the guidelines of the Church, said that unscrupulous politicians exploit the media spreading rant, and false information to justify the unfair political decisions. Present in the false light of their opponents, systematically distort or dissemble truth, using propaganda and invent. Rather than unite people, media are moving away from each other then them, creating a climate of tension and suspicion, which become spark political and social conflicts.In the light of the laws of the Catholic Church, among them the Internet does not need a new ethics, require only the application of established rules already in the new political situation.